DEVELOPMENT OF ARTICULATE STORYLINE 3-BASED INTERACTIVE LEARNING MEDIA FOR COMPUTER SYSTEMS SUBJECT: AN ADDIE-BASED DESIGN STUDY IN INDONESIAN VOCATIONAL EDUCATION - Jauhari Tamam; Abdul Haris Indrakusuma (STKIP PGRI TULUNGAGUNG, 2026)
The persistent reliance on conventional, teacher-centered instructional methods in Indonesian vocational secondary schools (SMK) has been identified as a contributing factor to low student engagement and suboptimal learning outcomes, particularly in technical subjects such as Computer Systems. This study addresses that gap by developing and evaluating an interactive learning medium for the Computer Systems subject at Class X Multimedia 2, SMK Islam 1 Durenan, using Articulate Storyline 3 as the development platform. The research employed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design model. Validation was conducted through expert review (material and media experts) and two-phase student trials (small group: n = 10; large group: n = 25). Quantitative data were collected via structured rating instruments and analysed using percentage feasibility scores. Results demonstrated that the developed medium achieved a material feasibility score of 85% (Very Feasible), a media feasibility score of 79% (Feasible), and student response scores of 72% and 80% for the small-group and large-group trials, respectively, both rated as Feasible. These findings confirm that the Articulate Storyline 3-based medium is both technically sound and pedagogically appropriate for vocational learners. The study contributes empirical evidence supporting the adoption of authoring-tool-based interactive media in vocational ICT education and provides a replicable development framework for practitioners and researchers in similar contexts